The relationship between synovitis quantified by an ultrasound 7-joint inflammation score and physical disability in rheumatoid arthritis - a cohort study - Závada, Jakub; Hánová, Petra; Hurňáková, Jana; Szczuková, Lenka; Uher, Michal; Forejtová, Šárka; Klein, Martin; Mann, Herman; Olejárová, Marta; Růžičková, Olga; Šléglová, Olga; Hejduk, Karel; et al. (Arthritis research & therapy, 2017)
BACKGROUND: Restoring normal physical functioning is a major therapeutic aim in the management of rheumatoid arthritis (RA). It is unknown, whether the extent of synovial inflammation quantified by musculoskeletal ultrasound (US) can predict current or future capacity for physical functioning. To answer this question we investigated the longitudinal relationship between physical function assessed by the health assessment questionnaire (HAQ) and the German 7-joint ultrasound score (US7S) in a prospective cohort of patients with RA. METHODS: Patients with RA (n = 185 (46 with incident and 139 with prevalent disease) were followed for 30.9 ± 9.1 months. Baseline and annual assessments comprised the disease activity score in 28 joints (DAS28), HAQ and US7S. The US7S includes semiquantitative measurements of synovitis assessed by greyscale (GS) and power Doppler (PD) in seven joints of the clinically dominant hand and foot, which are then aggregated in PD and GS synovitis sum-scores (PDsynSS and GSsynSS). A linear mixed-effect model was used to assess the longitudinal relationship between GSsynSS, PDsynSS and HAQ. We used standard and time-lag models to explore the association between HAQ, and GSsynSS, PDsynSS and DAS28 measured at the same time or at the previous visit 12 months ago, respectively. RESULTS: When the standard model was applied, in univariate analyses HAQ score was positively associated with GSsynSS and PDsynSS with β coefficients significantly higher in incident than in prevalent disease. In multivariate analysis both synSSs were individually no longer significant predictors of HAQ score. When using the time-lag model, after adjustment for the previous DAS28 or HAQ score, both PDsynSS and GSsynSS were significantly and negatively associated with the current HAQ. CONCLUSIONS: US7 PD and GS synovitis sum-scores alone were positively associated with current functional status reflected by the HAQ in patients with RA, and this relationship was stronger in patients with early disease. When combined with the DAS28 or HAQ, US7 PD and GS synovitis sum-scores were predictive of the change in HAQ score over one year.
Keywords: Surveys and Questionnaires; Disability Evaluation; Humans; lidé středního věku; posuzování pracovní neschopnosti; Arthritis, Rheumatoid; kohortové studie; Synovitis; Female; Aged; Inflammation; Ultrasonography; senioři; lidé; synovitida; Rheumatoid arthritis; zánět; průzkumy a dotazníky; Cohort Studies; revmatoidní artritida; ultrasonografie; ženské pohlaví; Male; Middle Aged; Health assessment questionnaire; mužské pohlaví